Rare case of primary esophageal synovial sarcoma with (x;18) translocation presenting as dysphagia - Sekaran, Anuradha; Shinde, Purva; Vanere, Veena; Ramchandani, Mohan; Reddy, Duvvur N. (International Journal of Research in Medical Sciences, 2021)
Synovial sarcoma (SS) in young adult mainly involves periarticular region of the extremities. Synovial sarcomas are exceedingly rare neoplasms of the digestive tract. In this report, we describe a very rare occurrence of primary SS of the esophagus in a 30-year-old female. Patient presented with dysphagia. Endoscopy showed submucosal esophageal polyp. Piecemeal polypectomy was done. Histologically, the tumor demonstrated biphasic morphology with epithelial and mesnchymal component. Tumor cells expressed pancytokeratin, bcl-2 and CD99 antigens. Differential diagnosis of synovial sarcoma and epithelial mesenchymal biphasic tumor was made. Cytogenetics was done to confirm the diagnosis of SS. It showed translocation (x;18). Synovial sarcomas are very rare tumor entities, particularly in the gastrointestinal tract and are likely to be mistaken with other more common tumors such as gastrointestinal stromal tumors.